2017
DOI: 10.3892/or.2017.5869
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the growth of hepatocellular carcinoma cells through fibroblast growth factor 18 suppressed by miR-139

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a highly malignant tumor and one of the most common causes for human cancer-related deaths. Fibroblast growth factor 18 (FGF18) is overexpressed in many types of cancer, and is associated with cell proliferation, invasion and angiogenesis. miR-139 has recently been reported as a tumor suppressor in various types of cancer and it can regulate many tumor-related genes, however its association with FGF18 expression in HCC has not been reported and thus remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…That miR-139 could inhibit the growth of HCC cells in cell experiments have been shown in previous studies [11][12][13]. To assess that miR-139 is a functional direct regulator of CBX3 in HCC cells, miR-139 mimics or miR-NC was transfected with SMMC-7721 and Herp-3B cells, followed by the combined effects of miR-139 and CBX3 overexpression were then investigated, the expression of CBX3 protein ( Figure 7A) in the miR-139 mimics group was dramatically decreased relative to that in the miR-NC group, and restored in the combined miR-139 and CBX3 overexpression group.…”
Section: Mir-139 Regulated Hcc Progression Through Directly Targetingsupporting
confidence: 62%
“…That miR-139 could inhibit the growth of HCC cells in cell experiments have been shown in previous studies [11][12][13]. To assess that miR-139 is a functional direct regulator of CBX3 in HCC cells, miR-139 mimics or miR-NC was transfected with SMMC-7721 and Herp-3B cells, followed by the combined effects of miR-139 and CBX3 overexpression were then investigated, the expression of CBX3 protein ( Figure 7A) in the miR-139 mimics group was dramatically decreased relative to that in the miR-NC group, and restored in the combined miR-139 and CBX3 overexpression group.…”
Section: Mir-139 Regulated Hcc Progression Through Directly Targetingsupporting
confidence: 62%
“…That miR-139 could inhibit the growth of HCC cells in cell experiments have been shown in previous studies [11][12][13]. To assess that miR-139 is a functional direct regulator of CBX3 in HCC cells, miR-139 mimics or miR-NC was transfected with SMMC-7721 and Herp-3B cells, followed by the combined effects of miR-139 and CBX3 overexpression were then investigated, the expression of CBX3 protein (Fig.…”
Section: Cbx3 Was a Direct Target Of Mir-139 In Hccmentioning
confidence: 68%
“…Moreover, in addition to finding that FGF18 is highly expressed in HCC tissues and cell lines, Li’s team also found that FGF18 mediates the regulation of miR-139 on HCC progression. These results indicated that FGF18 could mediate H19 non-coding RNA and miR-139 to promote the tumorigenic potential of HCC ( 34 ).…”
Section: The Role Of Fgf18 In Cancermentioning
confidence: 95%
“…In 2013, Wei's team predicted that overexpression of FGF18 was an independent marker for poor prognosis of ovarian cancer, and determined that FGF18 was a serum biomarker of ovarian cancer, which was significantly correlated with the prognosis and progression of ovarian cancer (33). In addition, the continuous discovery of FGF18 in different organs or systems is of great significance in guiding tumor progression, which indicates that FGF18 can be used as an oncogene reference for the progression of multiple systemic tumors (10, [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%